Analytical Approach to Predict Pre–Camber Deflection of the Pre-stressed Glulam Beams - Buan Anshari (Institute of Research and Community Outreach - Petra Christian University, 2015)
A new approach to reinforce glulam timber beams using compressed wood (CW) has been developed by the Author. The compressed wood blocks are inserted into pre-cut holes on the top of glulam beams to produce pre-camber and to generate initial tensile and compressive stresses on the top and on the bottom extreme fiber of the glulam beam, respectively. A simple analytical approach has been developed to predict pre-camber deflections of the beams reinforced with three CW blocks. Assuming that moisture-dependent expansion of the CW block creates an interactive linear pressure between the glulam beam and the CW block, this would generate a pair of eccentric force away from the neutral axis of the beam. It is shown that the pre-camber deflection predicted at midspan of the short beams with various reinforcing arrangements give good agreement with the measured pre-camber from previous experimental results.